Production Efficiency and Environmental Regulation: A Distance Function Approach - Okurut, Francis Tukei (My University, 2024)
Regulations can affect corporate behaviour in various ways, and this paper focuses on environmental regulations designed to limit the pollution of the atmosphere by carbon dioxide emissions. Tremendous debate has been generated regarding the effects of such regulation on firm efficiency and several methods to try and model firm behaviour under those conditions. Porter (1991) theorised that environmental regulations stimulate corporate innovation, creating a win-win situation for economic and ecological concerns. He pointed out that corporations could identify areas for improvement and take beneficial measures to enhance efficiency. This study models these two concerns to test for a win-win relationship using regression analysis. However, there is no evidence supporting this view. The primary method in this study was the ''Directional Distance Output Function,'' which models firm technology in a way that captures efficiency by treating output as an increase of the 'desirable' good and a reduction of the 'undesirable' bad. The test for a win-win relationship was conducted using regression analysis utilising the Directional Distance Output Function efficiency scores and a proxy for the stringency of regulation. This study does not, however, find supporting evidence that greater stringency in regulation was associated with higher firm efficiency. Although it was possible to show missed beneficial opportunities, it was not possible to identify specific areas that needed improvement.
Keywords: sustainable development; efficiency (properties); environmental effects; environmental policy; emissions; productivity; production; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance